2020
DOI: 10.3390/su12062358
|View full text |Cite
|
Sign up to set email alerts
|

How to Help Crowded Destinations: Tourist Anger vs. Sympathy and Role of Destination Social Responsibility

Abstract: Crowding at destinations is becoming an important issue in sustainable tourism. This study examines the relationship between tourist perceptions of crowding, environmentally responsible behavior (ERB), and intention to recommend a destination, from a helping behavior perspective. It proposes two discrete emotions, in particular anger and sympathy, to understand how tourist perceptions of crowding affect their helping behavior. We collected data through an online survey of tourists who had visited Jeju Island, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
(162 reference statements)
1
18
0
Order By: Relevance
“…The most frequently used theories as foundations of DSR research are the stimulus-organismresponse (SOR) framework and the social exchange theory (SET). SOR has been adopted in five articles (Kim & Yoon, 2020;Su & Swanson, 2017;Su, Swanson, & Hsu, 2018;Tran et al, 2018;Yu & Hwang, 2019). The SOR framework was introduced by Mehrabian and Russell (1974), who suggested that emotions and feelings guide people's behaviour.…”
Section: Theoretical Foundations Of Dsr Studiesmentioning
confidence: 99%
“…The most frequently used theories as foundations of DSR research are the stimulus-organismresponse (SOR) framework and the social exchange theory (SET). SOR has been adopted in five articles (Kim & Yoon, 2020;Su & Swanson, 2017;Su, Swanson, & Hsu, 2018;Tran et al, 2018;Yu & Hwang, 2019). The SOR framework was introduced by Mehrabian and Russell (1974), who suggested that emotions and feelings guide people's behaviour.…”
Section: Theoretical Foundations Of Dsr Studiesmentioning
confidence: 99%
“…Tourism has become an important part of the global economy, but with consequences for popular destinations and cities, overcrowding being one of the most prominent problems [1,2]. In addition to this, tourists are becoming accustomed to unsustainable forms of travel with high carbon footprints and negative impacts on air quality [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This type of tourist behavior has harmful effects on the environment. Therefore, the concept of environmentally responsible behavior (ERB) among tourists has been introduced in order to mitigate negative effects to the environment caused by tourist activities [2]. This concept is particularly relevant when bearing in mind that stopping all travel would damage destinations both economically and socially [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the newly involved settlements can benefit from growing visitor flow as well. This approach supports sustainability, since the spatial and temporal concentration of the tourists can be, to a certain extent, decreased in the Balaton region, and the wellbeing and life quality of the local population and the local economy can also be supported, together with the principle of the protection of the natural environment [17,18].…”
Section: Introductionmentioning
confidence: 99%